Active cell balancing for electric vehicle battery management system - Thiruvonasundari Duraisamy; Deepa kaliyaperumal (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
The shrink in accessibility of petroleum products and increment in asset request are eventual outcomes for Electrical Vehicles (EVs). The battery has an impact on the performance of electrical vehicles, the driving range. Lithium ion (Li-ion) chemistry is extremely sensitive to overcharge and deep discharge, which can harm the battery, shortening its period of time, and even inflicting risky things. The Battery Management System (BMS) comprises of the consequent parts: management, equalization and protection. Of the three components, equalization is that the most crucial with respect to the durability of the battery framework. The ability of the full pack diminishes rapidly amid the procedure which leads to degradation of the full battery framework. This condition is extreme once the battery incorporates a more number of cells in series and frequent charging is conveyed through the battery string. The cell imbalance during charging, discharging is a major issue in battery systems used in EVs. To circumvent the cell imbalance, cell balancing is used. Cell balancing enhances battery safety and extends battery life. This paper discusses about different active balancing method to increase the life span of the battery module. Based on the comparison, the inductor based balancing method for 60V battery system is implemented in the MATLAB/Simscape environment and the results are discussed.